2021
DOI: 10.3390/ijms222111515
|View full text |Cite
|
Sign up to set email alerts
|

Functional Availability of ON-Bipolar Cells in the Degenerated Retina: Timing and Longevity of an Optogenetic Gene Therapy

Abstract: Degenerative diseases of the retina are responsible for the death of photoreceptors and subsequent loss of vision in patients. Nevertheless, the inner retinal layers remain intact over an extended period of time, enabling the restoration of light sensitivity in blind retinas via the expression of optogenetic tools in the remaining retinal cells. The chimeric Opto-mGluR6 protein represents such a tool. With exclusive ON-bipolar cell expression, it combines the light-sensitive domains of melanopsin and the intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 66 publications
1
8
0
Order By: Relevance
“…Notably, the visual acuity and contrast sensitivity thresholds did not differ significantly in rd1 mice that were tested at an older age (Supplementary Fig. 6) which is in line with previously reported long-term functional preservation of optogenetic gene therapies 30 . These OMR data did not directly reflect the result of Fig.…”
Section: Resultssupporting
confidence: 90%
“…Notably, the visual acuity and contrast sensitivity thresholds did not differ significantly in rd1 mice that were tested at an older age (Supplementary Fig. 6) which is in line with previously reported long-term functional preservation of optogenetic gene therapies 30 . These OMR data did not directly reflect the result of Fig.…”
Section: Resultssupporting
confidence: 90%
“…The death of photoreceptors during degenerative retinal diseases, such as RP, ultimately leads to blindness [ 5 , 6 , 7 , 8 ]. OBCs, the first retinal interneurons downstream of the photoreceptors, were shown to survive for months to years after photoreceptor death [ 16 , 22 , 26 ], making them attractive targets for optogenetic vision restorative approaches [ 47 ]. Several optogenetic constructs have been introduced to OBCs to restore basic visual signaling [ 17 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is only one FDA-approved gene supplementation therapy available for genetic blindness, for patients specifically carrying the biallelic mutation of the RPE65 gene [ 9 ]. Given the heterogenous genetic origin of RP, other, more universal, therapeutic approaches are being explored, amongst them electronic prostheses [ 10 , 11 ], stem cell transplantation [ 12 , 13 ], expression of photo-switchable ligands [ 14 , 15 ], and optogenetic gene therapy [ 9 , 16 , 17 ]. Optogenetic gene therapy was shown to restore some visual function in a human patient [ 18 ] and in murine models of RP, particularly when targeted to the OBCs [ 19 , 20 , 21 , 22 ] such as Opto-mGluR6 [ 20 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Opto-mGluR6, a chimera of proteins of human origin, is about 500 times more light sensitive than ChR2 and naturally triggers endogenous TRPM1 signaling in ON-BPCs (van Wyk et al, 2015). We have previously demonstrated that the intravitreal injection of AAVs carrying the Opto-mGluR6 optogene under the control of the ON-BPC-specific GRM6 promoter (Hulliger et al, 2020) can restore visual function in otherwise blind retinal degeneration (rd1) mice (van Wyk et al, 2015;Kralik and Kleinlogel, 2021).…”
Section: Open Access Edited Bymentioning
confidence: 99%
“…For AAV vector generation, we used an AAV backbone with AAV2 ITRs while, for non-AAV vectors, we used the pIRES backbone. For details of vector composition, see (van Wyk et al, 2017;Hulliger et al, 2020;Kralik and Kleinlogel, 2021). The miniCMV promoter was derived from plasmid pX551-miniCMV-SpCas9 (Addgene plasmid # 107031).…”
Section: Plasmid and Aav Preparationmentioning
confidence: 99%